Republic of Albania : Final Country Procurement Assessment Report, Volume 2 - World Bank (Washington, DC, 2013)
The World Bank undertakes assessments of the procurement environment, covering both public and private sectors, in borrowing member countries on a systematic basis. The objective of this assessment is to provide useful feedback to Borrowers regarding the strengths and weaknesses of their public procurement systems. This enables member countries of the Bank to improve the transparency of their procurement processes and to develop an Action Plan to enhance their capacity to conduct public procurement efficiently. A further important objective is to determine the compatibility of national procurement practices with the principles of economy and efficiency and with international procurement law and best practice. The findings and recommendations of this report not only help the Bank to ensure that sound procurement practices are followed in projects which the Bank finances, but also enable Borrowers to enhance the efficiency of their public spending. The report makes these key recommendations: Strengthen the position of Open Tendering as the basic method of public procurement by bolstering the provisions in the LPP against breaking down procurement requirements into smaller values, providing fewer exceptions to the OT method and making all applications of procurement methods other than OT, above specified financial thresholds, subject to prior waiver of the Public Procurement Agency (PPA). . Clarify the conditions for use of restrictive procurement methods, including Restricted Tendering and Request for Quotations and strengthen the requirements for the minimum number of bids which procuring entities must obtain. Increase the use of the Request for Proposals (RFP) method for the procurement of consultants' services by removing the threshold that currently applies to it. More effectively control the current over-use of the Direct Procurement method by tightening the conditions for its use in the Law on Public Procurement (LPP) and by making all uses of this method subject to prior waiver by the PPA.